(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This is the third part of the bibliography of the magazine Women’s World: Magazine of Serbian Women’s Charity Associations. It covers four years in the publication of the magazine and includes 698 entries. As in the previous bibliographies, entries are organized in alphabetical order, according to the author’s last name or, in case the author is unknown or signed with initials, the name of the article. All entries exist in a shared database. Articles have been categorized and given a COBISS ID number. The number of texts on health decreased, but the number of texts on literature increased during these four years. For the first time since the establishment of the magazine, poems by Jovan Dučić, Aleksa Šantić, Svetozar Ćorović, etc. were published. Registers with title, name of the author and subject matter are provided.